Human Metabolites of Hamaforton™ (Hamamelis virginiana L. Extract) Modulates Fibroblast Extracellular Matrix Components in Response to UV-A Irradiation - Natella, Fausta; Guantario, Barbara; Ambra, Roberto; Ranaldi, Giulia; Intorre, Federica; Burki, Carolina; Canali, Raffaella (Frontiers in Pharmacology, 2021)
Hamamelis virginiana L. a rich source of both condensed and hydrolyzable tannins, utilized to treat dermatological disorders. Since no experimental and clinical data is available for its use as oral formulation in skin related disorders, the purpose of this study was to investigate the effects of Hamaforton™ (Hamamelis virginiana extract) metabolites on gene dysregulation induced by ultraviolet A radiation in cultured human dermal fibroblasts. A combination of in vivo and ex vivo experimental designs has been exploited in order to take into account the polyphenol metabolic transformation that occurs in humans. 12 healthy volunteers received either a capsule of Hamaforton™ or a placebo in a randomized, blinded crossover trial. After Hamaforton™ ingestion, the kinetic of appearance of galloyl derivatives was measured in plasma. Then, in the ex vivo experiment, the serum isolated after supplementation was used as a source of Hamaforton™ metabolites to enrich the culture medium of dermal fibroblasts exposed to ultraviolet A radiation. Three different gallic acid metabolites (4-O-methyl gallic acid, 4-O-methyl gallic acid sulphate and trimethyl gallic acid glucuronide) were identified in volunteer plasma. While, ultraviolet A irradiation of dermal fibroblasts affected the expression of extracellular matrix genes, the presence of Hamaforton™ metabolites in the culture media did not affect the expression of most of those genes. However, the activation of the expression of 10 different genes involved in repair processes for the maintenance of skin integrity, suggest that the metabolites can play a role in damage recovery. To our knowledge, this is the first study that demonstrates the bioavailability of Hamaforton™ phenolic compounds, and the effects of its metabolites on cultured dermal fibroblast response to ultraviolet A irradiation.